GREEN ROUTE SYNTHESIS OF COPPER OXIDE (CuO) NANOPARTICLES FOR THE DEGRADATION OF COMMERCIAL DYES USING VICIA FABA LEAF EXTRACT - P. Rastogi; Poonam Negi; Rawat, B.S; Naveen Chandra Joshi (Malaysian Journal of Science, 2024)
The release of toxic dyes into water effluents by various industries has become a global concern. Therefore, developing novel, straightforward, and economically viable methods or materials for purifying these hazardous pigments is imperative. This study aims to synthesize copper oxide nanoparticles (CuO-NPs) through a green route using Vicia faba leaf extract. UV-Vis spectroscopy reveals an absorption band ranging from 200 nm to 300 nm, with a major absorption peak at 212 nm and an energy band gap of 5.29 eV. FTIR, SEM, EDX, and XRD techniques characterise the synthesised CuO nanoparticles. FTIR analysis identifies functional groups including hydroxyl (OH), aromatic C-H, C=C stretching, carbonyl (C=O), and Cu-O stretching vibrations. Scanning electron microscopy reveals flower-like particles, while EDX analysis confirms the formation of CuO nanoparticles. The XRD pattern indicates a crystalline structure with an average particle size of 27.44 nm. A plot of (αhν)² versus photon energy (hν) was generated to determine the energy band gap, yielding a value of 5.29 eV. Rhodamine-B and methylene blue (MB) dyes were employed to evaluate the photocatalytic degradation of the synthesized CuO-NPs, resulting in correlation coefficients of 0.7154and 0.9702, respectively. Furthermore, the rate constants of these dye reactions were found to be 0.0406min-¹ and0.0343 min-¹.